The influence of physics laboratory standardization on the learning interest in physics - Fauzi Syaiful Kamal, Muhammad; Oktamaypasha, Rias; Kusmiatun, Ari; Susi Astuti, Tri; Sihono, Sihono; waraz (DRPM UNY, 2025)
The physics laboratory plays an essential role in science learning as it supports experiments that enhance students’ conceptual understanding and learning interest. This study aimed to analyze the standardization level of the physics laboratory at SMA Negeri 1 Turi and its relationship with the learning interest of grade X and XI students. A descriptive method with a mixed-methods approach using an Explanatory Sequential design was employed through observation, questionnaires, interviews, and documentation. The results showed that laboratory infrastructure (90%) and facilities (87%) were categorized as very good, while personnel (33%) were lacking and management (62.7%) was only sufficient. Laboratory implementation in learning scored (67.5%) in the good category, but its use as an assessment tool was not optimal. Questionnaires and interviews indicated that practicum activities increased students’ enthusiasm, although limited personnel and weak management made them irregular. Thus, the physics laboratory at SMA Negeri 1 Turi is very good in infrastructure and facilities but requires improvement in personnel and management to effectively support students’ learning interest.Keywords: laboratory standardization; management; learning interest; physics